Effects of moderate-intensity training exercise program on body composition and metabolic markers among overweight and obese dental students in Universiti Sains Malaysia - Sharan, Nursharlina (2024)
Overweight and obesity are global health issues that pose a threat to individuals in various professions, including dentistry. Dental practitioners often spend prolonged hours in a seated position while treating patients, placing them at a higher risk of developing low back pain. Studies have consistently reported that back pain has a strong correlation with overweight and obesity and significantly impacts the quality of life. Hence, it is crucial to raise awareness among dental students about the importance of maintaining a healthy body mass index (BMI) and lifestyle to prevent factors that contribute to back pain during their undergraduate studies and future dental practice. Objective: This study aimed to determine the effects of moderate-intensity training programs on body composition and metabolic markers among overweight and obese dental students of Universiti Sains Malaysia. Methodology: Thirty-three overweight and obese dental students (control, n=17 and exercise, n=16) were recruited, and their body composition and blood samples were collected pre- and post-intervention. Participants' 24-hour diet recalls were recorded. Students participated in 10 minutes of dynamic warm-up, followed by moderate-intensity Tabata exercise, carried out three times per week for 12 weeks, with an incremental increase in exercise duration every four weeks. Data was analysed using Independent T-test and Paired Sample T-test for normally distributed data and Mann-Whitney U test and Wilcoxon-Signed Ranked test for not normally distributed data. Results: After 12 weeks of intervention, the exercise group showed no significant differences in resting metabolic rate (RMR) of 1524.1±60.24 kcal/day (p>0.584), while their BMI remained stable at 27.8±0.88 kg/m2, indicating no significant change in body composition. Conversely, the control group showed a significant difference in BMI (p<0.034) which had increase in post-intervention (28.92±3.87 kg/m2). Both groups exhibited increases pattern levels of total cholesterol, triglyceride, HDL (high-density lipoprotein) and LDL (low-density lipoprotein) cholesterol, insulin, and IL-6 (interleukin-6) post-intervention. Additionally, the participants consumed high amounts of protein, fats, and sodium, exceeding the recommended nutrient intake (RNI). Conclusion: This study revealed that there were no significant differences in body composition between the control and exercise groups. However, the maintenance of BMI in the exercise group represents a positive outcome as it indicates that participants did not experience weight gain during the intervention. The investigation also detected increases pattern levels of total cholesterol, triglyceride, HDL and LDL cholesterol, insulin, and IL-6, a pro-inflammatory cytokine, in both group, which could be associated with excessive adipose tissue and high caloric intake. Therefore, future studies with stricter dietary restrictions are needed to determine the effects of moderate-intensity physical exercise on dental students' body composition